Об ограниченности напряжений в контактных задачах теории упругости - Мхитарян, С. М. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The article deals with the issue of determining the necessary dependencies between the characteristic elastic and geometric parameters that ensure the boundedness of the contact pressures (stresses) at the boundaries of the contact areas in the classical contact problems of the theory of elasticity, namely, in plane and axisymmetric problems, as well as in the problem of contact interaction of a stringer of finite length with an elastic half-plane. To determine the size of contact areas or other parameters when contact stresses are restricted, along with the widely used principle of continuity of contact stresses on smooth contact surfaces, the Castigliano energy principle is also used for elastic bodies, for which Hooke's law is valid. Based on the identity of the results obtained by both principles, their equivalence is shown. In addition, new results have been obtained for these two classical contact problems, supplementing those previously obtained. In the problem of the contact of a stringer with an elastic half-plane, by the principle of stress continuity, the conditions for the boundedness of contact stresses at the ends of a stringer are obtained only in two special cases. In addition, new results have been obtained for these two classical contact problems, supplementing those previously obtained. In the problem of the contact of a stringer with an elastic half-plane, by the principle of stress continuity, the conditions for the boundedness of contact stresses at the ends of a stringer are obtained only in two particular cases. Հոդվածում դիտարկվում է առաձգական և երկրաչափական պարամետրերի միջև անհրաժեշտ կախվածությունների որոշման հարցը, որոնք ապահովում են առաձգականության տեսության հարթ և առանցքահամաչափ դասական կոնտակտային խնդիրներում կոնտակտային լարումների սահմանականությունը՝ կոնտակտային տիրույթների եզրագծերի վրա։ Նույն հարցը քննարկվում է նաև վերջավոր երկարության վերադիրի և առաձգական կիսահարթության կոնտակտային փոխազդեցության խնդրում։ Կոնտակտային լարումների սահմանափակության դեպքում կոնտակ-տային տիրույթների չափերի կամ այլ պարամետրերի որոշման համար ողորկ կոնտակտային մակերևույթների դեպքում լայնորեն կիրառվող կոնտակտային լարումների անընդհատության սկզբունքին հավասար կիրառվում է նաև Կաստիլյանոյի էներգետիկ սկզբունքը առաձգական մարմինների համար, որոնք ենթարկվում են Հուկի օրենքին: Երկու սկզբունքներով ստացվող արդյունքների նույնական լինելու հիման վրա ցույց է տրված այդ սկզբունքների համարժեքությունը։ В статье рассматривается вопрос определения необходимых зависимостей между характерными упругими и геометрическими параметрами, обеспечивающих ограниченность контактных давлений (напряжений) на границах контактных областей в классических контактных задачах теории упругости, а именно, в плоских и осесимметрических задачах, а также в задаче контактного взаимодействия стрингера конечной длины с упругой полуплоскостью. Для определения размеров областей контакта или других параметров, когда контактные напряжения ограничены, наряду с широко применяемым принципом непрерывности контактных напряжений на гладких контактных поверхностях, применяется также энергетический принцип Кастильяно для упругих тел, для которых справедлив закон Гука. На основании идентичности результатов, полученных обеими принципами, показана их эквивалентность. Кроме того, по указанным двум классическим контактным задачам получены новые результаты, дополняющие ранее полученные. В задаче о контакте стрингера с упругой полуплоскостью условия ограниченности контактных напряжений на концах стрингера на основе принципа непрерывности напряжений получены лишь в двух частных случаях.
Keywords: Механика